Correction: Prevalence and factors associated with undernutrition among 15-49-year-old women in Sierra Leone: A secondary data analysis of Sierra Leone Demographic Health Survey of 2019. - PLOS One Staff (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0311845.].